Evaluating the Physical Mobility Levels and Well Being of Elders: Insights from the Countryside Setting of the Philippines - Fabillar, Jonas P.; Reposo, Madelynn N.; Sultan, Anecito A. (Universitas Ahmad Dahlan, 2025)
The pandemic significantly affected the health and well-being of elders, especially in disadvantaged communities. This study examines the physical mobility and well-being of elders aged 60-80 in Samar, Philippines. A descriptive research design was used to survey forty (40) voluntarily participating members of the Senior Citizens’ Organization. Physical mobility in both indoor and outdoor activities was assessed, with well-being self-reported by participants. Results showed a high percentage engaged in stretching and walking exercises, while the majority had irregular sleep patterns. However, many did not engage in household chores, market visits, or entrepreneurial activities. The study recommends establishing targeted educational and community-centric intervention programs among Local Government Units (LGUs) to enhance the physical health, cognitive functioning, and overall well-being of elders.